“DEVELOPMENT OF POST PANDEMIC EDUCATION TO FACE THE SOCIAL ERA 5.0”FUN AND ENJOYABLE WAYS TO LEARN MATHEMATICS IN ISLAMIC BOARDING SCHOOL - Siregar, Torang; Hilda, Lelya; Suparni, Suparni; Harahap, Sinar Devi (SINERGI : Jurnal Riset Ilmiah, 2024)
Lucky are the parents who send their children  to  Islamic  boarding  schools. Especially in this digital era, supervision of children needs to be enhanced. Learning in boarding schools is not only about religious knowledge but also other subjects, including Mathematics. However, many students claim that Mathematics is difficult. Various phenomena occur, such as students sleeping or skipping classes during Mathematics lessons, teachers who lack engaging lesson designs, and rigid and tense teaching methods that make Mathematics a frightening subject. As teachers, we should be able to create a fun and enjoyable learning atmosphere, so that students become addicted to learning Mathematics. The purpose of this research is to find out the fun and enjoyable ways to learn Mathematics in Islamic boarding schools. The analysis is based on literature review. Data collection techniques involve gathering various information from literature sources. Additionally, it is structured and organized systematically for better understanding. The results obtained in this research are various enjoyable ways to learn Mathematics in Islamic boarding schools.